2019
DOI: 10.1210/clinem/dgz006
|View full text |Cite
|
Sign up to set email alerts
|

Increased Infection Risk in Addison’s Disease and Congenital Adrenal Hyperplasia

Abstract: Context Mortality and infection-related hospital admissions are increased in patients with primary adrenal insufficiency (PAI). However, the risk of primary care–managed infections in patients with PAI is unknown. Objective To estimate infection risk in PAI due to Addison’s disease (AD) and congenital adrenal hyperplasia (CAH) in a primary care setting. Design … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 27 publications
2
53
1
Order By: Relevance
“…Although several studies have reported that AI itself may increase the risk of infection up to eight folds (43), the current evidence does not specifically support the fact that patients with AI are particularly prone to COVID-19. However, several plausible mechanisms are available, which may render patients with AI susceptible to COVID-19.…”
Section: Covid-19 and Adrenal Insufficiencycontrasting
confidence: 81%
“…Although several studies have reported that AI itself may increase the risk of infection up to eight folds (43), the current evidence does not specifically support the fact that patients with AI are particularly prone to COVID-19. However, several plausible mechanisms are available, which may render patients with AI susceptible to COVID-19.…”
Section: Covid-19 and Adrenal Insufficiencycontrasting
confidence: 81%
“…A population-based, retrospective, open cohort study in the United Kingdom from 1995 to 2018 showed that the Addison's disease cohort, compared with matched controls, had a higher risk of infections of the lower respiratory [adjusted incidence rate ratio (aIRR) 2.11; 95% CI 1.64-2.69], urinary (aIRR 1.51; 95% CI 1.29-1.77), and gastrointestinal (aIRR 3.80; 95% CI 2.99-4.84) tracts, leading to increased use of antimicrobial agents in the primary care setting [6]. Interestingly, the same study showed no increased risk of infection in patients with untreated congenital adrenal hyperplasia (CAH), but an increased infection risk in patients treated for CAH, suggesting that nonphysiological delivery of glucocorticoid replacement may represent a risk factor for the development of infections [6].…”
mentioning
confidence: 99%
“…However, when assessing the effect of age on androgen activation in peripheral tissues, age-related changes in the supply of androgen precursors from circulation need to be considered, in addition to age-dependent changes in the expression of androgen-activating and -inactivating enzymes in the peripheral target tissues of androgen action. While circulating levels of classic androgens significantly decline with age, levels of 11-oxygenated androgens remain constant across adulthood (29,30). Hence, the peripheral activation of 11-oxygenated androgens is favored over the activation of classic androgens not only by the substrate preference of the key androgen activating enzyme AKR1C3, but also by constant high substrate availability across the life span.…”
Section: Discussionmentioning
confidence: 99%